Time Series Analysis and Forecasting of Air Pollutants Based on Prophet Forecasting Model in Jiangsu Province, China - Hasnain, Ahmad; Sheng, Yehua; Hashmi, Muhammad Zaffar; Bhatti, Uzair Aslam; Hussain, Aamir; Hameed, Mazhar; Marjan, Shah; Bazai, Sibghat Ullah; Hossain, Mohammad Amzad; Sahabuddin, Md; Wagan, Raja Asif; Zha, Yong (Frontiers in Environmental Science, 2022)
Due to recent developments in the global economy, transportation, and industrialization, air pollution is one of main environmental issues in the 21st century. The current study aimed to predict both short-term and long-term air pollution in Jiangsu Province, China, based on the Prophet forecasting model (PFM). We collected data from 72 air quality monitoring stations to forecast six air pollutants: PM10, PM2.5, SO2, NO2, CO, and O3. To determine the accuracy of the model and to compare its results with predicted and actual values, we used the correlation coefficient (R), mean squared error (MSE), root mean squared error (RMSE), and mean absolute error (MAE). The results show that PFM predicted PM10 and PM2.5 with R values of 0.40 and 0.52, RMSE values of 16.37 and 12.07 μg/m3, and MAE values of 11.74 and 8.22 μg/m3, respectively. Among other pollutants, PFM also predicted SO2, NO2, CO, and O3 with R values of 0.17, 0.54, 0.38, and 0.66; RMSE values of 1.57, 6.72, 0.12, and 11.33 μg/m3; and MAE values of 1.16, 4.99, 0.09, and 8.84 μg/m3, respectively. PFM has extensive power to accurately predict the concentrations of air pollutants and can be used to forecast air pollution in other regions. The results of this research will be helpful for local authorities and policymakers to control air pollution and to plan accordingly in upcoming years.